Chloroplast genome structure analysis of Equisetum unveils phylogenetic relationships to ferns and mutational hotspot region - Sun, Weiyue; Wei, Zuoying; Gu, Yuefeng; Wang, Ting; Liu, Baodong; Yan, Yuehong (Frontiers in Plant Science, 2024)
Equisetum is the oldest extant group of vascular plants and is considered to be the key to understanding vascular plants evolution. Equisetum is distributed almost all over the world and has a high degree of adaptability to different environments. Despite the fossil record of horsetails (Equisetum, Equisetaceae) dating back to the Carboniferous, the phylogenetic relationship of this genus is not well, and the chloroplast evolution in Equisetum remains poorly understood. In order to fill this gap, we sequenced, assembled, and annotated the chloroplast genomes of 12 species of Equisetum, and compared them to 13 previously published vascular plants chloroplast genomes to deeply examine the plastome evolutionary dynamics of Equisetum. The chloroplast genomes have a highly conserved quadripartite structure across the genus, but these chloroplast genomes have a lower GC content than other fern plants. The size of Equisetum plastomes ranges from 130,773 bp to 133,684 bp and they encode 130 genes. Contraction/expansion of IR regions and the number of simple sequence repeat regions underlie large genomic variations in size among them. Comparative analysis revealed we also identified 13 divergence hotspot regions. Additionally, the genes accD and ycf1 can be used as potential DNA barcodes for the identification and phylogeny of the genus Equisetum. Twelve photosynthesisrelated genes were specifically selected in Equisetum. Comparative genomic analyses implied divergent evolutionary patterns between Equisetum and ferns. Phylogenomic analyses and molecular dating revealed a relatively distant phylogenetic relationship between Equisetum and ferns, supporting the division of pteridophyte into Lycophytes, Equisetaceae and ferns. The results show that the chloroplast genome can be used to solve phylogenetic problems within or between Equisetum species, and also provide genomic resources for the study of Equisetum systematics and evolution.